Tingkat Pemahaman Pengasuh dalam Menstimulasi Perkembangan Kognitif dan Sosial Emosional Anak Usia Dini di TPA Kecamatan Gunungpati: Caregivers' Level of Understanding in Stimulating Early Childhood Cognitive and Social Emotional Development in TPAs in Gunungpati Subdistrict - Aida Nur Afifah; Diana (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2026)
This study aims to determine the level of understanding of caregivers in stimulating children's cognitive and social emotional development. This study was conducted at the Child Care Center (TPA) in Gunungpati District, Semarang City, which was carried out in June 2025. This study uses a quantitative descriptive approach with a survey method. Data were collected through a 1-4 Likert scale questionnaire compiled based on child development indicators, supplemented by field observations, unstructured interviews, and documentation of children's activities. The subjects of this study were 31 caregivers. Using quantitative descriptive data analysis techniques. The results of the study show that the majority of caregivers have a very good understanding of cognitive aspects, such as encouraging children to tell stories, observing the environment, and recording children's thinking development periodically. However, understanding in social emotional aspects tends to be low, especially in terms of recognizing children's emotions and providing stimulation to form positive social skills. This finding emphasizes the importance of ongoing caregiver training that focuses not only on cognitive aspects, but also on a comprehensive understanding of children's emotions and behavior.   ABSTRAK Penelitian ini bertujuan untuk mengetahui tingkat pemahaman pengasuh dalam menstimulasi perkembangan kognitif dan sosial emoionak anak. Penelitain ini dilakukan di Tempat Penitipan Anak (TPA) Kecamatan Gunungpati, Kota Semarang yang dilaksanakan pada bulan juni 2025. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan metode survei. Data dikumpulkan melalui kuesioner skala likert 1-4 yang disusun berdasarkan indikator perkembangan anak, dilengkapi dengan observasi lapangan, wawancara tidak terstruktur, dan dokumentasi kegiatan anak. Adapun subyek penelitain dalam ini yaitu pengasuh sebanyak 31. Menggunakan teknik analisis data statistik deskriptif. Hasil penelitain menunjukan bahwa mayoritas pengasuh memiliki pemahaman yang sangat baik dalam aspek kognitif, seperti mendorong anak bercerita, mengamati lingkungan, serta mencatat perkembangan berpikir anak secara berkala. Namun, pemahaman dalam aspek sosial emosional cenderung masih rendah, khususnya dalam hal mengenali emosi anak dan memberikan stimulasi untuk membentuk keterampilan sosial yang positif. Temuan ini menegaskan pentingnya pelatihan pengasuh secara berkelanjutan yang tidak hanya berfokus pada aspek kognitif, tetapi juga pada pemahaman menyeluruh terhadap emosi dan perilaku anak.